Besedilo, branje, sklepanje - Justin, Janez (Šolsko polje, 2011)
One part of OECD-PISA project was conceived as a measurement of students' reading literacy. Students read short literary or expository texts and then answers questions concerning the content of the text. The author of the paper analysed the cognitive processes that resulted in the studentsć solving the task that they were given. Th e more diffi cult among the tasks required from the student to fill in the gaps in the texts they read with inferences they had made. We can distinguish between two groups of these inferences: 1. Inferences that produced some information in addition to the information conveyed by the texts; 2. inferences whose function was to bridge gaps in the texts. Before making the right inference, the student had to retrieve the right piece of information from their long-term memory. An inferential scheme had to be constructed that led the student to the solution of a task. While constructing such inferential schemes the student leaned upon the rules of natural logic they mastered early in their childhood.
Keywords: text; vzgoja in izobraževanje; reading literacy; bralna pismenost; natural logic; branje; education; bralnost; inference; naravna logika; sklepanje; PISA 2009; raziskave